Is counselling for CCAM that difficult? Learning from parental experience - Aite, Lucia (Journal of prenatal medicine, 2011)
OBJECTIVE: Cystic adenomatoid malformations (CCAM) are relatively rare developmental abnormalities of the lung. Despite outcome is usually benign, parents often exhibit high anxiety level. The purpose of the present study was to collect parents'subjective experience of communication of diagnosis when expecting a fetus with CCAM